KEDUDUKAN DISSENTING OPINION DALAM PERKARA TINDAK PIDANA KORUPSI - Rustam, Dewi Ratnasari (Lembaga Penelitian dan Pengabdian Masyarakat, 2018)
Dissenting opinion is the difference of opinion between the Tribunal judges who handle certain a matter with other judges of the Tribunal dealing with certain cases. Dissenting opinion does not have the force of law because it cannot be the Foundation for the inception of the award. Dissenting opinion itself is an aspect of the law that need to be examined in order to prevent the formation of false opinion among the public. So, nowadays have started to formed the perception that dissenting opinion was an engineering law, instead of enforcing the rule of law but rather media that gave the opportunity for the defendant in corruption regardless of criminal trapping; but on the other hand is a form of difference of opinion and the independence of the judges as the metre is guaranteed by the provisions of the law; that the importance of dissenting opinion in the Court ruling was the judge's opinion be weighted, in an attempt of law appeal or cassation; as an indicator to determine the career judge, as an attempt to avoid the practice of corruption, Collusion and Nepotism (KKN) and the judicial mafia; as a real step towards the transparency of judicial democratization; the judiciary; and kemandiarian the judge require the freedom of speech.